Expert evaluation of open-data indicators of seaport vulnerability to climate and extreme weather impacts for U.S. North Atlantic ports. (1st October 2019) - McIntosh, R. Duncan; Becker, Austin
Abstract: When comparing vulnerabilities of multiple disparate systems, indicator-based vulnerability assessment (IBVA) methods can yield standardized metrics, allowing for high-level analysis to identify areas or systems of concern. Identification of indicators is often a first step in the development of coastal vulnerability indices (CVI). To advance IBVA for the seaport sector, researchers investigated the sufficiency of and elicited expert-evaluation of publicly available open-data to serve as indicators of climate and extreme-weather vulnerability for 22 major seaports in the North East United States, addressing the question: How sufficient is the current state of data reporting for and about the seaport sector to develop expert-supported vulnerability indicators for a regional sample of ports? Researchers developed a framework for expert-evaluation of candidate indicators that can be replicated to develop indicators in other sectors and for other purposes. Researchers first identified candidate indicators from the climate change vulnerability assessment (CCVA) and seaport-studies literature and vetted them for data-availability for the sample ports. Candidate indicators were then evaluated by experts via a mind-mapping exercise, and finally via a visual analogue scale (VAS) measurement instrument. Researchers developed a VAS instrument to elicit expert perception of the magnitude and direction of correlation between candidate indicators and each of the three dimensions of vulnerability that have become standard in the CCVA literature, e.g., exposure, sensitivity, and adaptive capacity. For candidate indicators selected from currently available open data sources, port-expert respondents found notably stronger correlation with the exposure and sensitivity of a port than with the adaptive capacity. Results suggest that more open reporting and sharing of port-specific data within the maritime transportation sector will be necessary before IBVA will become feasible for seaports. Highlights: Open-data can be developed into expert-supported indicators of seaport climate exposure and sensitivity. Experts found relatively little perceived correlation between open-data candidate indicators and a port's adaptive capacity. Experts found higher levels of perceived correlation for place-based indicators than for port-specific indicators. Results suggest that more open sharing of port data within the maritime sector will be necessary before IBVA methods become feasible for seaports.